Analysis of Inventory Control of Green Spinach (Amaranthus Tricolor l) Seeds With Economic Order Quantity Method in CV. AMATTA MULYA BARIZI - Anisa Syifa Salsabila; Kuswarini Sulandjari; Ekalia Yusiana (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to identify inventory control and costs incurred by the company, analyze inventory cost control for green spinach seeds using the EOQ model VII method, and analyze cost efficiency for green spinach seed inventory. Methodology: The analysis used the EOQ method to determine the optimal order quantity for green spinach seeds at CV Amatta Mulya Barizi. Results: The EOQ method resulted in an optimal order quantity of 2,280 grams per order. The inventory costs for green spinach seeds amounted to IDR 273,642.00 per order or IDR 3,283,704.00 per year. Findings: The study found that the EOQ method is more efficient compared to the company’s current method, allowing the company to save IDR 586,296.00 annually on green spinach seed inventory costs. Novelty: This research provides new insights into the application of the EOQ model VII for seed inventory management, highlighting significant cost savings. Originality: The study offers a detailed analysis of inventory control and cost efficiency for green spinach seeds, contributing to better inventory management practices. Conclusions: The EOQ method is more efficient for inventory management of green spinach seeds at CV Amatta Mulya Barizi, resulting in considerable cost savings. Type of Paper: Empirical Research Article